(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aimed to identify the requirements for implementing green training in Libyan educational institutions in light of the orientation toward sustainable development, through a case study of the National Institute of Administration, It also sought to determine the availability of the administrative, technical, and human requirements necessary for implementing green training, identify the major obstacles hindering its implementation, and examine its role in achieving sustainable development. The study adopted the descriptive analytical approach. The study population consisted of all employees of the National Institute of Administration, totaling 30 employees, A comprehensive survey method was employed, whereby questionnaires were distributed to all members of the population, A total of 25 valid questionnaires were retrieved and analyzed, Statistical analysis software was used to calculate means, standard deviations, and Cronbach’s Alpha coefficients to verify the reliability of the research instrument. The findings revealed a low level of availability of the administrative, technical, and human requirements necessary for implementing green training, with technical requirements recording the lowest level among the studied dimensions. The results also indicated the presence of significant obstacles hindering the implementation of green training, mainly represented by limited financial resources, insufficient technical support, poor planning, and a lack of awareness regarding the concept of green training. Conversely, the findings showed a high level of employees’ awareness of the importance of green training and its role in enhancing environmental awareness, rationalizing resource consumption, improving organizational performance, and supporting the achievement of sustainable development goals. The study concluded that the successful implementation of green training requires the provision of a supportive organizational, technical, and human environment, as well as addressing the obstacles that hinder its application. The study recommended adopting an integrated green training strategy, developing technical infrastructure, enhancing financial and technical support, and promoting a culture of environmental sustainability among employees, thereby supporting the orientation toward sustainable development in Libyan educational institutions.